The restoration of the Kirillovsky parish and the work of the abbot Basil Krasovsky (1605-1614) on the revival of the Cyril Church - Margolina, Irina (Ukrai͏̈ns'ke relihijeznavstvo, 1999)
In the ancient chronicles we find interesting testimonies of the Cyril Monastery and the activities of prominent figures related to the history of this monastery. But notorious for Kyiv in 1240, this story ends in three long, hard ages. Among the experts do not abandon discussions on the most fundamental problems of this section of Ukrainian history. He seems to have fallen out of public memory: in the minds of our contemporaries, between Batu's invasion and Khmelnychchina, as a rule, there is a clear emptiness, although events occurring in this period lacked neither drama, nor historical greatness.